IMPROVING STUDENT LEARNING RESULTS IN MATHEMATICAL LEARNING THROUGH SOMATIC, AUDITORY, VISUAL AND INTELLECTUAL APPROACH (SAVI) - Ovan Adohar; Ramlan Mahmud; Ruslan B (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
This research was aimed to improve the Somatic,  Auditory, Visual, and Intelectual (SAVI) approach to Grade  Seven B (VII B) Bajiminasa. The Type of research used is classroom action research with classroom action research. The subject of this study was the students is class VIII Bajiminasa Makassar, South Sulawesi. of SMP Islam Sultan Agung 4 Semarang, Central Java. The writer analyzed the data with quantitative and qualitative approaches  on learning outcomes. The resulth of the study showed that the Somatic, Audotory, Visual and Intelectual (SAVI) approach was complete and student learning outomes had increased. To complete and improve in learning outcomes, presumably provide special guidance and do not experience improvement